2016
DOI: 10.1038/srep30380
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy nanostructure growth on Ta/Fe by He plasma irradiation

Abstract: In this study, we show from helium (He) plasma irradiation to tantalum and iron surfaces that morphology changes in nanoscale occur on the both metals. In particular, from systematic irradiation experiments, it is identified that fuzzy nanostructures are grown on the both metals. The necessary conditions for the morphology changes are discussed based on the experimental results in terms of the helium migration, the physical sputtering, and the shear modulus of materials. Because oxides or oxinitrides of iron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Linear fiber growth was also observed on Re surface 3406065-2 exposed to He plasma at high surface temperature [9]. It is noted that the crystal structure of Ru and Re is HCP.…”
Section: Ruthenium (Ru)mentioning
confidence: 71%
See 1 more Smart Citation
“…Linear fiber growth was also observed on Re surface 3406065-2 exposed to He plasma at high surface temperature [9]. It is noted that the crystal structure of Ru and Re is HCP.…”
Section: Ruthenium (Ru)mentioning
confidence: 71%
“…And a molecular dynamics (MD) simulation showed that yield strength of W fiber reduces significantly when He atoms were embedded [8]. Following these studies, the relationship between fuzz formation and shear modulus was discussed [9]; the fuzz was easily formed on high shear modulus metals such as W, Molyb- denum (Mo) and rhenium (Re), [10][11][12]. However, morphology changes induced by He plasma irradiation were not well-researched in other high shear modulus metals including rhodium (Rh) and ruthenium (Ru), which are facecentered cubic (FCC) and hexagonal close-packed (HCP), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was hypothesized that higher aspect ratio surface structures (similar to fuzz) could be formed at higher fluences since surface pores are known to be a precursor to fuzz formation in W 9 . To our knowledge, fuzz formation has never been observed in Ta except for in a very recent study23 that showed for the first time fuzz formation in Ta using sufficiently high He + ion fluences.…”
mentioning
confidence: 86%
“…Hence, it was proven that these plasma exposed surfaces do not only have a large surface area, but are also catalytically active. Kajita et al also studied the morphology development during plasma exposure for possible water splitting application using Fe and Ta bulk pellets recently [13]. For water splitting and many other 4 energy applications, however, thin films and not bulk material are used as electrodes due to costs, materials scarcity, and integration reasons.…”
Section: Introductionmentioning
confidence: 99%